Scheduling problems with rejection in green manufacturing industry - Kong, Fanyu; Song, Jiaxin; Miao, Cuixia; Zhang, Yuzhong (Journal of combinatorial optimization, 2025)
Green manufacturing is used to describe an environmentally friendly manufacturing approach, which explicitly considers the impact of production on the environment and resources. Therefore, the production scheduling of solving energy conscious is in line with the focus of green manufacturing. In this paper, we consider the scheduling problems with rejection in the green manufacturing industry. The objective is to minimize the makespan of the accepted jobs plus the total rejection penalty of the rejected jobs, subject to the constraint that the total machine cost of the processed jobs is not more than a given threshold. We present pseudo-polynomial time algorithms and 2-approximation algorithms for the single-machine and the parallel-machine problems, respectively.